OPTIMALISASI STORAGE SPACE DAN RAK PAJANG PRODUK PADA TOKO XYZ - Yosy Cynthia Miranda (Parsimonia - Jurnal Ekonomi dan Bisnis, 2018)
Project optimization of storage space and product display rack carried out from December 1, 2016 until December 14, 2016 at Store XYZ. The author was assigned to make the 3 sub rack coffee as a sample project. The project aims to maximize space management at XYZ store by way of rearranging existing carton in a small storage and lower buffer on each sub-rack in accordance with the demand of consumers every day. For 2 weeks, optimizing project and buffer storage space under the stack of cartons way to fix this is proven to increase sales by 39%. These quantities have successfully fulfilled an indicator of increased purchase quantity of products to be achieved, of the execution of this project, the author can recommend the store XYZ to record the re-arrangement of the carton according to the demand of consumers in each product, eliminating products that have long been empty and Noteworthy anyway time for refilling, particularly for pareto products. Pareto product is a fast moving products, or products with a high turnover than sales of other products.